CHANGES IN LANGUAGE USE OF JAVANESE WEDDING IN PRESERVING KAWI LANGUAGE IN KENDAL, CENTRAL JAVA - WIDIYANTO, TOMY (International Journal Multidisciplinary (IJMI), 2024)
A qualitative research that explained the linguistic phenomena in Kendal Regency, Central Java. The data sources were divided into two: primary and secondary. The primary data resource was a video recording of Pambiwara speeches in Javanese weddings, while the secondary data was in the form of library documentation and Javanese wedding. The purposes of this research were: (1) to describe the changes in language use of Javanese wedding in preserving Kawi language in Kendal, Central Java, (2) to describe the facts of Kawi Language use in Javanese wedding by Pambiwara, and (3) to observe changes and modifications in the language use of Javanese wedding for the maintenance of the Kawi language of Pambiwara. The Pambiwara produced 2000-3000 vocabulary words. Based on the average number of words issued by the Pambiwara in a Javanese wedding ceremony, the percentage occurrences of the Kawi language vocabulary also varied. It could also be seen that there were changes and modifications of the order of Javanese marriages into a more concise and simpler order used by Pambiwara to use Prasaja Javanese which belonged to simple and easy to understand Javanese language. Keywords : Javanese wedding, kawi language, pambiwara.